2021
DOI: 10.1371/journal.pntd.0009533
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic nanoporous silicon carrier improves the efficacy of buparvaquone against resistant visceral leishmaniasis

Abstract: Visceral leishmaniasis is a vector-borne protozoan infection that is fatal if untreated. There is no vaccination against the disease, and the current chemotherapeutic agents are ineffective due to increased resistance and severe side effects. Buparvaquone is a potential drug against the leishmaniases, but it is highly hydrophobic resulting in poor bioavailability and low therapeutic efficacy. Herein, we loaded the drug into silicon nanoparticles produced from barley husk, which is an agricultural residue and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…These results demonstrate that the synthesis of NanoSi was successful and the optimal NanoSi was produced by the 1:1 reaction system of formaldehyde and resorcinol with TEOS at 550 °C. NanoSi surfaces with a rough hairy material, as well as the existence of empty structures and surface voids, could serve as excellent nanocarriers for target materials, thereby improving its bioavailability. , For example, the parasite inhibition rate of bubatroxone loaded onto NanoSi was close to 100% . Therefore, this spherical hairy material might be an excellent nanocarrier for many materials.…”
Section: Resultsmentioning
confidence: 99%
“…These results demonstrate that the synthesis of NanoSi was successful and the optimal NanoSi was produced by the 1:1 reaction system of formaldehyde and resorcinol with TEOS at 550 °C. NanoSi surfaces with a rough hairy material, as well as the existence of empty structures and surface voids, could serve as excellent nanocarriers for target materials, thereby improving its bioavailability. , For example, the parasite inhibition rate of bubatroxone loaded onto NanoSi was close to 100% . Therefore, this spherical hairy material might be an excellent nanocarrier for many materials.…”
Section: Resultsmentioning
confidence: 99%
“…Thapa and co-workers produced mesoporous silica (MSNPs) from barley ash, an agricultural industry residue, and observed a significant in vivo reduction of L. donovani parasite burden by incorporating buparvaquone (BPQ) into the MSNPs. 198 Buparvaquone, a drug with poor water solubility, benefits from improved bioviability when delivered through MSNPs, potentially reducing the toxicity associated with BPQ. The authors found that the BPQ-loaded MSNPs exhibited good biocompatibility, increasing the CC 50 by ca.…”
Section: Acs Infectious Diseasesmentioning
confidence: 99%
“…Buparvaquone is a promising leishmaniasis medication, although it has low bioavailability and therapeutic efficacy due to its hydrophobic nature. The parasite burden was nearly completely decreased by intraperitoneally administered buparvaquone-loaded (biogenic silicon nanoparticles) silicon nanoparticles made from barley husk, an agricultural residue that is commonly available [150].…”
Section: Other Pathways Of Leishmania Parasite Targeted By Various Dr...mentioning
confidence: 99%